RECORD OF THE FAMILY CALANIDAE (COPEPODA : CALANOIDA) WITH NOTES ON ITS MORPHOLOGICAL VARIABILITY AND DISTRIBUTION IN INDONESIA WATERS - Mulyadi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1999)
Some species of calanoid copepods of the family Calanidae inhabit surface or moderately deep waters, and provide excellent material for zoogeographic investigations. Very few studies on the taxonomy and morphological variability of the family Calanidae from Indonesian waters have been carried out. The present paper deals with relevant information on description and illustrations of five calanid species from the region. Five of previously known species, i.e., Canthocalanus pauper (Giebrecth, 1888); Undinula vulgaris (Dana, 1849); Casmocalanus darwini (Lubbock, 1860); Neocalanus gracilis (Dana, 1849); and Calanoides philippinensis (Kitou & Tanaka, 1969) have been recorded. Descriptions, measurements and figures are given for all these species, along with a review of their distribution over the world's oceans, and with taxonomic remarks, morphological variability, and synonymies.